Ocena realizacji programu SAPARD w województwie warmińsko-mazurskim - Czeszejko-Sochacka, Małgorzata; Wojarska, Magdalena (Assessment of the SAPARD Program Realization in Warmia and Mazury Voivodship, 2005)
SAPARD stands for Special Accession Programme for Agriculture and Rural Development. In the framework of SAPARD, the European Union supports measures to promote agriculture and rural development in the ten candidate countries of Central and Eastern Europe. A specificity of SAPARD is the decentralised administration of programmes. Administrative tasks usually performed by the Commission were delegated to the authorities of the respective third country.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 114-119